Pemanfaatan Google Docs dalam Kolaborasi Real-Time Pembelajaran Menyunting Teks - Masyithah Maghfirah Rizam; Kristanti Ayuanita (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
Group text editing is done manually when dealing with printed text, so the process certainly uses more paper and is not practical. So, the use of Google Docs in real-time collaborative learning to edit text needs to be done to overcome the impracticality of editing using printed text. When learning to edit text in groups, it will also be more practical, effective and efficient if you use Google Docs. Google Docs can connect editors at one time to edit text together. The advantage is of course that it is more sophisticated than editing the respective printed text which then still needs to be discussed and retyped. Through Google Docs, typing is done in real-time.